A division-wide framework to scaffold the development of English language and intercultural learning - Nallaya, Sasikala; Hobson, James (Journal of Academic Language and Learning, 2021)
This paper reports on a case study that was undertaken to inform the creation of a Division-wide English Language and Intercultural Learning and Teaching (ELILT) Framework in the university where the authors work. Participants’ insights on their current experience with English Language Proficiency (ELP), Intercultural Learning (IL) and Knowledge Exchange (KE) development were to be employed to create the ELILT Framework so that the future development of these capabilities in programs and courses can be undertaken systematically. Data was collected through a mixed-method approach. Ninety-five undergraduate and postgraduate students participated in an online survey administered through Survey Monkey and seven students took part in semi-structured interviews. It was found that more could be done by the University to meet students’ learning needs, impacted by their linguistic and cultural diversity. Some students from multilingual backgrounds could benefit from support in the development of their ELP for academic studies. The study highlighted that while Learning Advisers located in the Central Learning and Teaching Unit played a significant role in generic language and literacies development, some students were unable to access learning support for various reasons and would rather have this development occur in their courses and study program, directed by their course coordinators. The investigation also suggested that more needs to be done to scaffold the development of intercultural orientation and awareness for all students and staff in the University to foster relationships between language, culture, and learning so that meaningful engagement with diversity can unfold within and outside the University.